2022
DOI: 10.1109/access.2022.3179421
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Hammerstein Spline Adaptive Filtering Based on Orthogonal Gradient Adaptive Algorithm

Abstract: In this paper, we propose a class of nonlinear diffusion filtering based on Hammerstein function with the spline adaptive filter (HSAF) implemented by normalised version of orthogonal gradient adaptive (NOGA) algorithm over the distributed network. Diffusion adaptation algorithm approximates a variable vector with the help of a network of agents using a joint optimisation on the sum of cost function. A HSAF comprises of memoryless function during learning by interpolating polynomials with respect to the linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…The According to nonlinear cooperative adaptation, the diffusion spline adaptive filterings in [16] have shown that they can perform well in comparison with the non-cooperative network. Sitjongsataporn [17] a class of nonlinear diffusion adaptive filtering has been furnished in the framework of orthogonal gradientbased algorithm. While, the combined diffusion affine algorithm has been presented over the distributed networks [18], Merched [19], [20] has derived with the diffusion adaptation to fuse data based on least squares mechanism against the colored inputs in the single-task and multi-task scenes.…”
mentioning
confidence: 99%
“…The According to nonlinear cooperative adaptation, the diffusion spline adaptive filterings in [16] have shown that they can perform well in comparison with the non-cooperative network. Sitjongsataporn [17] a class of nonlinear diffusion adaptive filtering has been furnished in the framework of orthogonal gradientbased algorithm. While, the combined diffusion affine algorithm has been presented over the distributed networks [18], Merched [19], [20] has derived with the diffusion adaptation to fuse data based on least squares mechanism against the colored inputs in the single-task and multi-task scenes.…”
mentioning
confidence: 99%